Experience Quality: A Hybrid Systematic Literature Review and Bibliometric Analysis (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Although Experience Quality has been extensively researched, comprehensive studies remain limited. This research aims to conduct a Systematic Literature Review (SLR) and bibliometric analysis of existing empirical work on Experience Quality. The methodology used is SLR, with data collected from the Scopus database using the search term "Experience Quality" in the title, abstract, and keywords. This search yielded 1,297 publications from 1965 to 2025 (evaluated on October 24, 2025). The data were analyzed bibliometrically using VOSviewer. The findings confirm that experience quality has a significant effect on brand perception and customer satisfaction, which consequently impacts customer loyalty. Practically, this implies that brand and service managers must treat experience quality as a strategic variable, as good products or services alone are insufficient for long-term loyalty. Socially, positive experiences are shown to strengthen social networks, increase community involvement, and promote inclusion. This research is limited by its reliance solely on the Scopus database; future research should integrate additional databases, such as Web of Science, for broader generalization. Despite the global development of this topic, in-depth, structured studies are scarce. This research is valuable and original as it provides a comprehensive summary and a research roadmap through SLR and bibliometric analysis.